Technical and economic aspects of biomass co-firing in coal-fired boilers - Dzikuć, Maciej; Łasiński, Krzysztof (Zielona Góra: Uniwersytet Zielonogórski)
The article presents the analysis of the potential of using biomass and coal co-firing in the Polish electro energetic system and shows the benefits resulting from an increase of biomass amount in electricity production in one of the largest Polish power stations.
Keywords: biomass; coal; co-firing; energy; economy